The role of the family in spread of the phenomenon of violence in the adolescent - Alaa Aldeen, Raneem (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This study aims to identify the specific family factors for violence, the sample of this study consists of (214) students from Latakia city schools. The results of the study indicated the existence of a relationship between each of: (the income level of the family, the nature of the relationship between the spouses, the nature of the relationship between parents and children, the educational level of the mother) and teen violence. While the study showed that there is no relationship between each of: ( the educational level of the father, the confidence of the teen parents, the absence of one the parents) and teen violence. The study reached to wide lines can be taken into account, which could contribute to the rehabilitation of future youth.